Från generell bild till individuellt ansikte: att hantera oförståelse och stereotypt bemötande i fyra lågstatusyrken (Sociologisk Forskning, 2010)
From general images to individual features: managing lack of understanding and stereotypes in four low-status occupationsIndividuals shape an image of themselves and their surroundings in relation to how they assume that others regard them. In these situations occupation is essential. Categorizations, valuations and rewards associated with occupations are among the most fundamental instruments used for domination in the social world. Hence it is interesting to study how groups and individuals who experience low occupational status manage their social positions. This article, based upon interviews with workers in food industry, waitresses/waiters, storesmen and dustmen, analyzes how the interviewees handle low respect, here expressed as lack of understanding and stereotyping. Three different positions are distinguished, arguing that one of them implies a stronger identification with the occupation than do the other two, which to a greater extent agree with stereotyped images. In the first position, the workers disagree with stereotypes of low-status jobs as apathetic, heavy or simple, and assert that their occupation has specific values such as self-development, qualifications or advantage to society. In the second position, low recognition is avoided through little identification with the occupation. The interviewees separate themselves and who they are from their jobs, and find it ridiculous to speak about it in terms of self-development or qualifications when so many are able to do the job. In the third position, the interviewees emphasize that their own place of work is less heavy than the job in general. Through the third strategy their particular tasks are seen as exceptional and their identification with the occupation is local rather than embedded in a wider occupational identity.